2018
DOI: 10.1155/2018/9828023
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Enzyme-Linked Immunosorbent Assays (ELISAs) in Detecting Antibodies againstMycobacterium lepraein Leprosy Patients: A Systematic Review and Meta-Analysis

Abstract: IgM against Mycobacterium leprae may be detected by enzyme-linked immunosorbent assays (ELISAs) based on phenolic glycolipid I (PGL-I) or natural disaccharide octyl bovine serum albumin (ND-O-BSA) as antigens, and the IgG response can be detected by an ELISA based on lipid droplet protein 1 (LID-1). The titers of antibodies against these antigens vary with operational classification. The aim of this study was to compare the accuracy of ELISAs involving PGL-I and ND-O-BSA with that involving LID-1. We included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…ApoA1 inhibits the recruitment of monocytes and macrophage chemotaxis ( 22 ), whereas CRP can recognize pathogens and activate the classical complement pathway ( 23 ). Together with αPGL-I IgM, the well-established biomarker for MB leprosy ( 24 ), the identified biomarkers were implemented in quantitative up-converting phosphor lateral flow assays (UCP-LFAs) ( 19 ). These user-friendly tests are applicable in resource-limited settings, essential for diagnostic tools in large-scale contact screening of leprosy contacts, and provide quantitative results.…”
Section: Introductionmentioning
confidence: 99%
“…ApoA1 inhibits the recruitment of monocytes and macrophage chemotaxis ( 22 ), whereas CRP can recognize pathogens and activate the classical complement pathway ( 23 ). Together with αPGL-I IgM, the well-established biomarker for MB leprosy ( 24 ), the identified biomarkers were implemented in quantitative up-converting phosphor lateral flow assays (UCP-LFAs) ( 19 ). These user-friendly tests are applicable in resource-limited settings, essential for diagnostic tools in large-scale contact screening of leprosy contacts, and provide quantitative results.…”
Section: Introductionmentioning
confidence: 99%
“…The use of diagnostic tests has been largely discussed. A meta-analysis study regarding the accuracy of ELISAs in detecting antibodies against mycobacterium leprae concluded that traditional ELISAs have good accuracy in detecting MB leprosy and poor accuracy in detecting PB leprosy 40 . Another meta-analysis evaluating diagnostic accuracy of tests concluded that although the test accuracy looks reasonable, the studies suffered from heterogeneity and low methodological quality 41 .…”
Section: Discussionmentioning
confidence: 99%
“…IgM may be detected by enzyme-linked immunosorbent assays (ELISAs) based on phenolic glycolipid I (PGL-I) or natural disaccharide octyl bovine serum albumin (ND-O-BSA) as antigens; IgG response can be detected by an ELISA based on lipid droplet protein 1 (LID-1). A recent metanalyses showed no advantages in the overall estimated sensitivity for isolated LID-1 compared to PGL-I or ND-O-BSA 14 . In terms of outlook, validating and introducing serological tests with anti-PGL-I and natural disaccharide octyl and lipid droplet protein 1 (NDO-LID) combination for field use might support the diagnosis 14 .…”
mentioning
confidence: 93%
“…A recent metanalyses showed no advantages in the overall estimated sensitivity for isolated LID-1 compared to PGL-I or ND-O-BSA 14 . In terms of outlook, validating and introducing serological tests with anti-PGL-I and natural disaccharide octyl and lipid droplet protein 1 (NDO-LID) combination for field use might support the diagnosis 14 . Although additional biomarkers have been identified, validating and implementing their use remain challenging, and there is no reliable and rapid point-of-care (POC) test on the horizon.…”
mentioning
confidence: 93%